ANALISIS SALURAN TATANIAGA DAN MARJIN TATANIAGA KELAPA DALAM (Cocos Nucifera) DI KABUPATEN TANJUNG JABUNG BARAT PROVINSI JAMBI - Siti Abir Wulandari (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
This research purposed to know about some marketing  channel of coconut product and marketing margin of some coconut Middlemens in Tanjung Jabung Barat. The Middlemen type in this research was a sales agent that usually deal with a person that bought some coconuts directly  from the farmer to be sale back to the further  Middlemen type. Sampling method ( 42 Middlemens ) was conducted by   multistage sampling,  combining with a snowball sampling method. The result of this research indicated that there were  two kinds  marketing channel of coconut product in Tanjung Jabung Barat. The average farmer price was Rp. 1.199,-/unit and it shoud be traded of on Rp. 1.489,-/unit. So that the marketing margin of some coconut  Middlemens in Tanjung Jabung Barat showed Rp. 234,-/unit coconut.Keywords: coconut, marketing, channel and margin